PENGARUH PENERAPAN STRATEGI BELAJAR AKTIF TIPE GIVING QUESTION AND GETTING ANSWER (GQGA) TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS XII IPS SMA NEGERI 16 PADANG TAHUN PELAJARAN 2013/2014 - Ningsih, Selvia Rahayu; Rahmi, Rahmi; Husna, Husna (Pendidikan Matematika, 2013)
This research is done due to the fact that most of students do not dare to ask about learning material, in oral ways, which is not understood so that students become less active and lack of mastering mathematical concept. This study is aimed to determine how students learning activities are done and to find out whether the understanding of studentsâ mathematical concept become better by using active learning strategy âGiving Questions and Getting Answers (GQGA)â than the conventional ones. The type of this research is experimental research; with the design of the research is Randomized Subject. The population of this research is students of grade XII Social Science at SMAN 16 Padang which consist of four classes. In determining the experimental class and the control class, researcher chooses it randomly, so that XII Social Science 1 is chosen as experimental class, and XII Social Science 2 as control class. The instruments that are used in this study are studentsâ activity observation sheet and the test of studentsâ understanding for mathematical concept. Based on the result of the study, it is found that implementing active learning strategy âGiving Questions and Getting Answers (GQGA) have increasing percentage in each meeting. The result of analysis data find out that two sample classesÂ Â  normal distributed and homogenous at the level of Î± = 0,05 and the result of t test is obtained P-value = 0,020, smaller than Î± = 0,05, so that hypothesis is approved.